Preparing pharmacy faculty through a postgraduate year one pharmacy residency program that includes a master of science in education degree. Issue 2 (14th November 2022) - Ray, Sarah; Johnson, Chris; Lokken, James; Johnson, Francesca Napolitano; Traynor, Andrew
Abstract: An effective pharmacist workforce requires highly qualified and effective pharmacy educators. Qualifications required of pharmacy practice faculty may vary by academic institution but the American College of Clinical Pharmacy recommends completion of a residency or fellowship that includes structured teaching experiences and scholarly activities. Although teaching and learning certificate programs may offer a way for residents to gain this experience, program quality may vary and there is evidence that department chairs and other administrators may value additional advanced degrees over these certificate programs. However, less than 20% of the faculty surveyed obtained an additional degree beyond the Doctor of Pharmacy. Advanced degree programs are also a relatively uncommon component of pharmacy residency programs, with a Master of Science in Health‐System Pharmacy Administration being the most common. The first year of an innovative postgraduate 24‐month pharmacy practice residency program that includes completion of a Master of Science in Education degree offers the breadth and depth of ambulatory care practice, teaching, service, and research/scholarship that is beneficial for pharmacists seeking pharmacy practice faculty appointments. Eight key residency elements critical for success are detailed. A description of core coursework highlighted the intentional design of the Master of Science in Education degree program. Previous resident graduates reflected on the value of the Master of Science in Education degree program and the overall pharmacy residency program. This unique post‐graduate training program may serve as a model for preparing pharmacy practice faculty.